Revitalisasi Nilai Sosial dalam Hadis: Telaah Living Hadis di Era Digital - Sari, Winda (UIN Sumatera Utara Medan, 2025)
Social values in Hadith such as brotherhood, justice, empathy, and mutual assistance serve as the ethical foundation for interpersonal relationships within society. In the digital era, the dissemination of Hadith has become increasingly widespread through various social media platforms. However, this transformation is often not accompanied by a deep understanding and actualization of its intrinsic values. This study aims to examine how social values in Hadith are being revitalized through the living Hadith approach in the digital era. Using a qualitative library research method, the data were analyzed through hermeneutic and sociology of knowledge perspectives. The findings reveal that while the circulation of Hadith in digital media tends to be symbolic and superficial in meaning, it simultaneously opens new opportunities for actualization through inclusive and participatory digital practices. Textual reinterpretation and contextual reapplication are key strategies in restoring the social function of Hadith as a guide for modern life. This study recommends the development of digital religious literacy, value-based da'wah, and integrative approaches in enhancing the living Hadith tradition in the information age.